A Review of Global Management and Procurement: Impacts on Sustainability and Cost-Effectiveness in Architectural Projects (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This proposal presents a study that seeks to understand the influence of global procurement on sustainability and cost-effectiveness in architecture. The research is relevant to architecture, as it aligns with the increasing globalization of architectural projects, necessitating efficient procurement strategies. The study aims to investigate the impact of global sourcing on environmental sustainability and cost considerations. The proposed research will review pertinent theories on international procurement and sourcing. It will analyze existing literature on global procurement practices in architecture, focusing on sustainability and cost-effectiveness. By identifying existing gaps in research on this topic, the study will also help to direct future investigations and discussions. The study’s significance is further underpinned by its potential to enhance sustainable and cost-effective procurement practices in the architectural industry. The anticipated contributions of this research include an exploration of the integration of sustainable practices into global procurement processes and its impact on environmental outcomes, as well as an examination of the interplay between sustainable procurement practices and project cost-effectiveness.